Analisis Pengaruh dan Kontribusi Pajak Daerah serta Retribusi Daerah Terhadap Peningkatan Pendapatan Asli Daerah - Samie Lambert Jacobs; Jusak Ubjaaan; Maximiliane Hukom (Univiversitas Dr. Djar Wattiheluw, 2022)
This study aims to measure the level of effectiveness and contribution of local taxes and regional levies to Ambon city's own-source revenue (PAD). The analysis model used is descriptive qualitative and quantitative analysis. The analysis used is an effectiveness analysis to determine the level of effectiveness of applying regional tax contributions and regional levies in the city of Ambon from 2017 to 2021 for the last five years. Based on the calculation of the effectiveness of regional levies, the contribution of local revenue is less than 100. point level. On the other hand, the contribution of local taxes and surcharges to local own-source revenues has increased over the last five years based on local revenues, but their effectiveness has decreased. The calculated contribution to effectiveness in 2017 is 0.22% and the contribution for 2018 is 0.23%. On the other hand, down 0.19% in 2019. 0.19% in 2020. Up 0.22% in 2021.